Tool Support for Scenario-based Functional Allocation - Sutcliffe, Alistair G.; Shin, Jae Eun; Gregoriades, Andreas (My University, 2002)
Tool support is described for analyzing requirements and creating conceptual models from scenarios. A schema of scenario-based knowledge is proposed that extends the i* ontology with concepts to represent the system environment and natural language semantics to categorize arguments. Modelling tools are introduced to support the process of transforming scenarios into models and requirements. We illustrate use of the tools by analysis of the London Ambulance case study. The advisor guides the analyst with contextual appropriate advice on functional allocation of agent roles and generic requirements to avoid errors and system failure. The advice is based on research in human reliability engineering
Keywords: scenarios; functional allocation; socio-technical systems; human error